Relasi Sufisme dan Politik pada Masyarakat Mataraman di Kediri - Taufik Alamin (Teosofi: Jurnal Tasawuf dan Pemikiran Islam, 2016)
Since the thirteenth century AD, the presence of a new model of Sufism, neo-Sufism, has impacted the infiltration of political identity in the spiritual flow of the tarekat practicing society. The spiritual world of Sufism has experienced a paradigm shift in thinking, from what was originally a movement that balances the hereafter and the worldly things, but in the end this movement is also considered very pragmatic-contextual that enters the socio-political dimension. This article wants to provide a new understanding of how the balanced relationship between Sufism and politics occurs in the Mataraman community, Kediri, East Java. By using the non-participant observer technique, this article produces two things: first, the political culture formed in the Kediri Mataraman society has a centralized pattern, where both tarekat congregations and ordinary people devote themselves to any field of social problems to a kiai. Sufi kiai becomes the main role models because they are considered pious people for the Mataraman community. This recognition of the Sufi kiai figure forms a group of socio-political systems. Second, the political pyramid that developed in the people of Kediri City follows a hierarchical-centralized pyramid pattern, where the kiai/murshid tarekat are ordained as the movers and creators of the foremost political culture after the Kediri city government and business bureaucrats. This pattern of social structure becomes the link so that leadership can be achieved and become the material for formulating political strategies.